Telemental and Telebehavioral Health Considerations: A 50-State Analysis on the Development of Telehealth Policy - Lerman, Amy F.; Kim, Daniel; Ozinal, Francesca R.; Thompson, Theresa E. (Telehealth and Medicine Today, 2018)
Contemporary healthcare delivery models have a patient-centered approach, a focus on integrating the various types of services patients need, an emphasis on interdisciplinary treatment teams, and a commitment to adopting innovative technologies. Increasing utilization of telehealth technologies has helped foster these contemporary service delivery models by improving access to healthcare services, leveraging the expertise of specialty providers to the point-of-service, and enhancing opportunities for healthcare professional and consumer education. As such, telehealth delivery models have become mainstream and viable solution for healthcare providers, physicians, and employers. According to an August 2016 report from the U.S. Department of Health and Human Services, an estimated 61% of healthcare institutions use some form of telehealth technology, and between 40% and 50% of all hospitals in the United States employ some form of telehealth technology. 1Following suit, the provision of telebehavioral or “telemental” health services continue to trend upward, as behavioral health providers become more interested in utilizing telehealth platforms to connect with their patients. Mental illness affects millions of individuals in the U.S., from all walks of life and across all age groups, contributing significantly to the burdens of disease.2 While mental illness can be recurrent and serious, often it is treatable, provided affected individuals have access to necessary resources. Patients surveyed regarding their use of telemental health services express consistent and affirmative beliefs that telemental health services provide positive benefits. Surveys report little or no difference in levels of patient satisfaction compared to face-to-face interactions between patients and their behavioral health providers.3,4 As states continue to support and expand the exciting benefits telehealth technologies and services offer, our legislators, healthcare systems, and regulatory bodies are being tasked with working together to navigate the numerous legal and regulatory issues that come with it. Epstein Becker Green (“EBG”) recently released an Appendix to its “50-State Survey of Telemental/Telebehavioral Health (2016),” with new and updated analysis on the laws, regulations, and regulatory policies affecting the practice of telemental/telebehavioral health in all 50 states and the District of Columbia.5 The 2017 Appendix reflects the incredibly active legislative efforts in most states with respect to the provision of telehealth services. In fact, only two states, Connecticut and Massachusetts, have not made changes to their legal and regulatory framework since the 2016 Survey. This suggests a lot of policy activity among states to regulate and provide meaningful guidance to telehealth providers.